Bacterial identification of the vaginal micro biota and presence of pathogens causing bacterial vaginosis during pregnancy in Bangladeshi women - Hasan, Md Mahmud; Sultana, Mashyat; Khan, Tasnova Tabassum (Brac University, 2022)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Microbiology, 2022.